Blue Rubber Bleb Nevus Syndrome as a Cause of Lower Digestive Bleeding - Carlos Augusto Real Martinez; Murilo Rocha Rodrigues; Daniela Tiemi Sato; Paulo Pedroso Silveira Júnior; Rafael Fernandes Gama; Christian Bornia Mattavelli; José Aires Pereira (Case Reports in Surgery)
Introduction. Blue rubber bleb nevus syndrome is a rare disorder that is characterized by multiple recurrent vascular malformations that involve the skin and the gastrointestinal tract. The disease can present chronic anemia and severe episodes of gastrointestinal bleeding. Case Report. A 41-year-old man was admitted with recurrent episodes of lower gastrointestinal bleeding and anemia that had worsened over the last 3 months. The physical examination showed soft, diffuse, compressible, bluish nodules on all of the skin surfaces of the body. A biopsy from one of these skin lesions allowed a histological diagnosis of cavernous hemangioma. He submitted to a colonoscopy, which showed hemorrhoids and a plane vascular lesion mainly located on the right colon with recent signs of bleeding; this lesion was treated by local excision and sclerosis. The pathological study of the colon specimens also reflected the presence of cavernous hemangioma. The cutaneous hemangiomas and the presence of colonic venous malformations were compatible with blue rubber bleb nevus syndrome. The patient presented a favorable follow-up with clinical control of the anemia and without relapse of the gastrointestinal bleeding two years after the procedure. Conclusion. Although rarely diagnosed, blue rubber bleb nevus syndrome may be responsible for lower digestive bleeding.